Cryptoeconomics: Financial Market Security Aspects and Implications for Managerial Accounting - Stashchuk, Olena; Kulynych, Myroslava; Tesliuk, Sofiia; Kupyra, Myroslava; Dorosh, Viktoriia; Vahnovska, Nataliya (AESSRA, 2024)
The development of modern information technologies and the processes of globalization are key factors for the emergence and spread of virtual currency. The legal status of cryptocurrency is still uncertain. It is considered both as a modern means of payment and as a speculative tool for illegal activities. However, despite such diametrically opposed interpretations, the fact that economic realities are constantly changing is unconditional. The IFRS reporting system is no exception, which should adapt to new challenges in a timely manner and take into account the need to disclose information about new progressive elements as much as possible. The article aims to analyze the economic and financial essence of cryptocurrencies, assess the phenomenon of the crypto economy and its impact on the financial market and monetary policy, as well as to outline appropriate implications for the corporate level – namely, for management accounting. The methodology is based on a theoretical analysis of cryptographic protocols and tools for investment and macroeconomic analysis, some approaches of economic theory. It is shown that although today cryptocurrency is a speculative, high-risk instrument, cryptoeconomics is increasingly integrating into the global financial market, while the potential risks of this process still outweigh its benefits. Accordingly, at the micro-level, management accountants must understand the related risks and be able to explain the implications to the management team and the board of directors. The originality of research consists of an attempt to combine the analysis of macro- and micro-implications of emerging crypto economics based on an economic theory foundation.
Keywords: Cryptoeconomics; Cryptocurrency; Financial market; Bitcoin; Risk; Security; Regulation; Management Accounting; Enterprise; Digitalization; Financial Information; G 18